Autonomous low limb exoskeleton to suppress the body weight - Mir-Nasiri, Nazim; Jo, Hudyjaya Siwoyo (2017 3rd International Conference on Control, Automation and Robotics (ICCAR), 2017)
The paper describes conceptual design, control strategies and full simulation for a new fully autonomous lower limb exoskeleton system for human motion enhancement. The exoskeleton supports the subject weight and provides an additional strength and endurance to the subject. The designed exoskeleton is able to decouple the weight/mass carrying function of the system from its forward motion function. This newly proposed approach effectively reduces the power and size of propulsion motors and thus the overall weight, cost of the system. It also allows the exoskeleton to operate for extended periods without being frequently recharged. The decoupling takes place by placing a passive air cylinder across the joint and blocking the motion at knee joint. The cylinder is actuated when the weight on one leg reaches the maximum predetermined value. The mechanism of the exoskeleton features a seat to rest the subject's body weight at that particular moment. However, it is the subject that responsible for moving the legs in swinging motion. The flexible sensors attached to the subject legs together with the hip and knee motors help to prevent obstruction caused by the exoskeleton structure to the subject leg in free swinging motion. The motors force the system to precisely follow the subject's leg motion in the swinging stage due to the close-loop controller with the feedback from flexible sensors. The mechanical structure of each leg has six degrees of freedom: four at the hip, one at the knee and one at the ankle. This exoskeleton is power efficient because the smaller electrical motors are used to drive the exoskeleton mechanical system and do not to support the weight like in the most of the existing exoskeleton designs.